Efektivitas Ekstrak Spirulina platensis terhadap Jumlah Fibroblas pada Tikus yang Dilakukan Insisi pada Kulitnya - Riski dwi utami; olvaria misfa; Bimby Irenesia; deinike wanita marwan (Indonesian Journal of Pharmaceutical Education, 2023)
Fibroblasts play a role in the wound healing process. The active compound content of Spirulina sp. has fibroblastic activity. The use of extracts from S. platensis can play a role in the wound healing process. To analyze the effectiveness of Spirulina platensis extract on the number of fibroblasts in rats that were incised in their skin. This study used a randomized post test only control group design. Forty-eight male Wistar rats were skin incised and infected with S.aureus divided into 4 groups, namely the group given S.platensis extract at a dose of 500 mg/kgBW/day, a dose of 750 mg/kgBW/day, the negative control group was given saline solution and positive control group with diclofenac 20 mg/kgBW orally. The number of fibroblasts was counted on histopathological examination of the wound tissue on the 7th and 14th days covering 5 visual fields. Data analysis was carried out with a one way ANOVA test and continued with the LSD Post Hoc Test. The mean number of fibroblasts on the 7th day in the 500 mg/kgBW/day group, 750 mg/kgBW/day, positive control and negative control was 13.33 ± 3.615; 117.42±3.980; 9.58±2.417; and 4.00 ± 1.761 with p 0.001. The number of fibroblasts on the 14th day in the 500 mg/kgBW/day, 750 mg/kgBW/day group, positive control and negative control was 16.17 ± 3.251; 19.67±1.633; 12.17±2.137; and 8.33 ± 2.317 with p 0.001. The post hoc test found that the number of fibroblasts on day 7 significantly increased in the 500 mg/kgBB/day S. platensis group compared to the positive and negative control groups. While at a dose of 750 mg/kg/day, the number of fibroblasts was higher than the positive and negative control groups after 14 days of treatment.Administration of Spirulina platensis extract at doses of 500 and 750 mg/kg/day significantly increased the number of fibroblasts in the incision wounds of Wistar rats.